Integrasi Gaya Kepemimpinan Kepala Sekolah Dalam Membentuk Ekosistem Pendidikan Vokasi Berbasis Islam di SMK Muhammadiyah 4 Surakarta - Qoriib, Ahmad Fathun; Shobahiya, Mahasri (Kamaya: Jurnal Ilmu Agama, 2026)
This research is motivated by the strategic role of the principal as a builder of a professional and religious work ecosystem in an Islamic-based vocational education institution. The purpose of this study is to explore the leadership model implemented by the principal of SMK Muhammadiyah 4 Surakarta in managing vocational education based on Islamic values. The research method used is descriptive qualitative through field research with data collection techniques in the form of structured interviews, direct observation, and document review. Data analysis adopted the Miles and Huberman framework which includes information condensation, presentation of results, and formulation of conclusions. The results show that the principal applies an integrative-contextual leadership style that harmoniously combines four main approaches: transformational, servant leadership, collective-collegial, and distributed. The transformational element is reflected in the development of vision and motivation for innovation; the servant aspect is seen in empathy and commitment to teacher competency development; the collegial-participatory approach is manifested in the deliberation mechanism; and distributed leadership is carried out through the delegation of balanced authority to the management team. This leadership model has a positive impact on improving academic standards, strengthening the religious atmosphere, and aligning graduates with the demands of the workplace. The study’s conclusions confirm that leadership effectiveness in Islamic vocational schools is determined by the leader’s ability to be adaptive and multidimensional in responding to the institution’s internal and external dynamics.